COMMENTARIES ON THE ARTICLE «MODERN CAPABILITIES OF IMMUNOPROPHYLAXIS OF ACUTE RESPIRATORY INFECTIONS IN FREQUENTLY AILING CHILDREN» BY N.A. KOROVINA ET AL. - A.V. Karaulov (Union of pediatricians of Russia, 2008)
.